Older Adult Patients’ Convalescence and Recovery within One Week after Abdominal Surgery at Thammasat University Hospital - Penphumphuang, Issarapong; Matchim, Yaowarat; Mahawongkajit, Prasit (Journal of The Royal Thai Army Nurses, 2020)
This study aimed to examine older adult patients’ convalescence and recovery within one week after abdominal surgery. The study participants were 60 older adult patients undergoing major gastrointestinal surgery. The tools used for screening the participants included: 1) the Short Portable Mental Status Questionnaire (SPMSQ), and 2) the Activities of Daily Living index (ADL). The instruments used for collecting the data included: 1) a demographic data form, and 2) the Convalescence and Recovery Evaluation (CARE) measure. Descriptive statistics were used to analyze the data. The results showed that the participants had convalescence and recovery within one week after abdominal surgery for each dimension as follows: 1) pain domain—the highest score for pain in the abdominal and belly area (M = 4.83, SD = .38); 2) the gastrointestinal domain—the highest score for bloating and gassiness (M = 3.36, SD = .55); 3) the cognitive domain—trouble concentrating (M = 3.00, SD = .55) and forgetful (M = 2.53, SD = .59); and 4) the activity domain—the participants could perform light activities during the second and fourth day after abdominal surgery (M = 2.40, SD = .69). The activity domain considered the recovery is slow. The participants with colorectal diseases had the highest scores for pain and gastrointestinal domains, whereas the participants with hepatobiliary diseases had the highest scores for cognitive and activity domains. The results of this study can be used for developing programs to enhance recovery after abdominal surgery for older adult patients.